2020
DOI: 10.1371/journal.ppat.1009007
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin forces and the energetics of red blood cell invasion by the malaria parasite Plasmodium falciparum

Abstract: All symptoms of malaria disease are associated with the asexual blood stages of development, involving cycles of red blood cell (RBC) invasion and egress by the Plasmodium spp. merozoite. Merozoite invasion is rapid and is actively powered by a parasite actomyosin motor. The current accepted model for actomyosin force generation envisages arrays of parasite myosins, pushing against short actin filaments connected to the external milieu that drive the merozoite forwards into the RBC. In Plasmodium falciparum, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 74 publications
(149 reference statements)
1
34
0
Order By: Relevance
“…Live imaging of microgametogenesis revealed that the erythrocyte membrane likely undergoes echinocytosis in preparation for egress, as evident from the formation of small, spiked projections on the cell surface (Fig 2C). Although echinocytosis is an established feature of asexual blood stage development post-invasion [37], the phenomenon is reported here as a feature of microgametocyte-egress, for the first time. Activated microgametocytes aligned at the periphery of the parasite membrane and eventually ejected from a frequently singular pore that formed in the host erythrocyte (Fig 2C and S3 Video).…”
Section: Host Erythrocyte Pore Formation and Possible Echinocytosis I...mentioning
confidence: 63%
“…Live imaging of microgametogenesis revealed that the erythrocyte membrane likely undergoes echinocytosis in preparation for egress, as evident from the formation of small, spiked projections on the cell surface (Fig 2C). Although echinocytosis is an established feature of asexual blood stage development post-invasion [37], the phenomenon is reported here as a feature of microgametocyte-egress, for the first time. Activated microgametocytes aligned at the periphery of the parasite membrane and eventually ejected from a frequently singular pore that formed in the host erythrocyte (Fig 2C and S3 Video).…”
Section: Host Erythrocyte Pore Formation and Possible Echinocytosis I...mentioning
confidence: 63%
“…Three different components of the glideosome were conditionally knocked out in three independent studiesnamely PfACT1 (Das et al, 2017), PfMyoA (Blake, Haase, & Baum, 2020) and PfGAP45 (Perrin et al, 2018), and in each of these cases, a complete abrogation of invasion was observed. These observations may be explained by the relatively larger size of the nucleus in comparison to the merozoite, differences in shape of the merozoite and tachyzoite, differences in stiffness of the erythrocyte membrane compared to other mammalian cell membranes, or by different requirements of the Plasmodium invasion machinery compared to Toxoplasma.…”
Section: Furthermore Analysis Of F-actin Dynamics During Invasion Ofmentioning
confidence: 99%
“…While the role of PfMyoA in the movement of the parasite had been established 5 , it was only recently shown that PfMyoA is essential for invasion of red blood cells by merozoites, the stage responsible for the symptoms of malaria 3 . PfMyoA thus represents an efficient pharmaceutical target since blocking its activity would impair both the motile and invasive stages of the parasite 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%